Pengaruh Konseling Kreatif Dance and Movement dan Percaya Diri terhadap Kebahagiaan Remaja di Panti Asuhan Terima Kasih Abadi Medan - Otto Mart Andreas; Sri Milfayetty; M. Rajab Lubis (Jurnal Multidisiplin Madani, 2022)
This paper aims to determine the differences in the happiness of orphanages who are given dance and movement creative counseling services and those who are given conventional counseling services, the differences in the happiness of orphans who have high self-confidence and those who have low self-confidence, and the interaction between dance creative counseling and Movement and self-confidence in influencing the happiness of the orphanage youth. The problem is focused on the happiness of the orphanage youth who are given dance and movement creative counseling services. To approach this problem, Seligman's Authentic Happiness theory is used as a reference. The data were collected through the scale of happiness and self-confidence and analyzed by means of a two-way ANOVA with a significance level of 0.05. This study concludes that there is a difference in the happiness of the orphanage youth who were given Dance and Movement creative counseling services and those given conventional counseling services with Fcount>Ftable, namely 9.32; the difference in the happiness of orphans who have high self-confidence and those who have low self-confidence with Fcount>Ftable is 29.07; and found the interaction between Dance and Movement creative counseling and self-confidence towards the happiness of the orphanage youth with Fcount > Ftable, namely 5.84.